2017
DOI: 10.1088/1555-6611/aa741c
|View full text |Cite
|
Sign up to set email alerts
|

S-band Q-switched thulium fluoride fiber laser using graphene saturable absorber

Abstract: A Q-switched S-band thulium fluoride fiber (TFF) driven by a 1400 nm laser diode is proposed and demonstrated. The TFF has the advantage of being pumped at 1400 nm, which is an easily available and relatively low-cost pump source, as opposed to conventional pumping at 1050 nm. It has a gain profile from 1440 nm to 1520 nm, and Q-switching is realized with the use of a thin film graphene saturable absorber. The Q-switched TFF laser exhibits a maximum repetition rate and minimum pulse width of 36.3 kHz and 3.2 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Similarly, Reduan et al [46] also showed an output with a larger pulse width of 3.8 µs using a molybdenum disulphide (MoS 2 )-based SA than the obtained pulse width of 3.2 µs of this work. The Q-switched laser in this work has the same pulse width as that of the cavity using the graphene-based SA [41], which also showed a lower pulse energy of 35.8 nJ than the laser of this work. From table 1, it can be seen that the Cu 2 Te SA generates among the highest maximum pulse energy and maximum average output power in the S+/S band region, with only the MoS 2 SA performing similarly.…”
Section: Resultsmentioning
confidence: 76%
“…Similarly, Reduan et al [46] also showed an output with a larger pulse width of 3.8 µs using a molybdenum disulphide (MoS 2 )-based SA than the obtained pulse width of 3.2 µs of this work. The Q-switched laser in this work has the same pulse width as that of the cavity using the graphene-based SA [41], which also showed a lower pulse energy of 35.8 nJ than the laser of this work. From table 1, it can be seen that the Cu 2 Te SA generates among the highest maximum pulse energy and maximum average output power in the S+/S band region, with only the MoS 2 SA performing similarly.…”
Section: Resultsmentioning
confidence: 76%